Diatom biostratigraphy of ODP Holes 191-1179B and 191-1179C - Diane M Winter; James Arney; Sherwood W Wise (PANGAEA, 2005)
Although the objective of Ocean Drilling Program Leg 191 was to install a seismic monitoring station and to test a hard rock reentry drilling system, several good, near-continuous sedimentary core sequences were recovered during the cruise. Two holes, 1179B and 1179C, yielded an upper Miocene to Pleistocene diatom record through an expanded section with excellent recovery. Because diatom species included in both low-latitude and high-latitude biostratigraphies are present, zonations for the equatorial Pacific and northwest Pacific are applied to the sediments. The oldest zones from each zonation that are represented in the cores are the Nitzschia miocenica Zone and the Rouxia californica Zone, respectively. Only one zonal boundary is not observed within the diatom assemblage, that being the top of the Nitzschia jouseae Zone and base of the Rhizosolenia praebergonii Subzone A (equatorial Pacific). Preservation is good overall, and sample abundances vary from rare to abundant. This would be an excellent section for further biostratigraphic, paleoclimatic, and paleoceanographic study.
Supplement to: Winter, DM et al. (2005): Upper Miocene-Pleistocene diatom biostratigraphy in the northwest Pacific, ODP Leg 191. In: Sager, WW; Kanazawa, T; Escutia, C (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 191, 1-39, https://doi.org/10.2973/odp.proc.sr.191.009.2005